ENTREPRENEURIAL ALERTNESS AMONG SMALL SCALE ENTREPRENEURS: THE ROLE OF CREATIVITY AND INTUITION - Ebeh, Richards E (African Journal of Social and Behavioural Sciences, 2020)
The purpose of this study was to investigate the roles of creativity and intuition on the entrepreneurial alertness of 220 entrepreneurs who were drawn from markets in Enugu, Enugu State, Nigeria. Participants comprised of 125 males and 95 females with ages ranging from 20 to 75 years (M = 37.23; SD = 11.24). Three instruments were used; a modified Creativity Styles Questionnaire – Revised (CSQ-R) by Kumar, Kemmler and Holman (1997), a self developed Entrepreneurial Intuition Scale (EIS) and a modified Entrepreneurial Alertness Scale by Tang, Kacmar and Busenitz (2012). The Cross-Sectional Survey Design was employed while hierarchical multiple regression statistics was used to analyze data collected. Findings showed that entrepreneurial alertness of small scale entrepreneurs was significantly predicted by their level of creativity. However, intuitiveness did not significantly predict small scale entrepreneur’s level of entrepreneurial alertness. The study reaffirmed the need for psychologists offering vocational guidance and counselling services to intending entrepreneurs to consider assessing the level of creativity of their clients as being creative can enhance entrepreneurial alertness which is germane to developing successful business organisations.